The Effect of Internal Motivation and External Motivation on the Performance of Employees of the Population and Civil Registration Service of - Jaitun Jaitun; Inka Nusamuda Pratama (Visi Pencerah Nusantara, 2025)
This study aims to determine the partial influence of internal and external motivation on employee performance at the Population and Civil Registration Office of Bima Regency. To determine the simultaneous influence of internal and external motivation on employee performance at the Population and Civil Registration Office of Bima Regency. This study employs a quantitative method, utilizing data collection techniques that include distributing questionnaires to a sample of 57 respondents, drawn from a population of 67. The sampling technique used was non-probability-based target sampling. The instrument was tested for reliability, validity, and analysis prerequisites. Based on the study's results, which were analyzed using multiple regression analysis with SPSS version 22 for Windows, the overall results for each partial test indicate that the variables are significant and influential. Based on the calculated F-value of 5.029 with a significant p-value of 0.001 (<0.05), it can be concluded that there is a simultaneous influence of Internal Motivation and External Motivation on Employee Performance. The results show that all independent variables together have a significant influence on the dependent variable, with a significance value of 0.001 (p < 0.05). The magnitude of the simultaneous influence between independent and dependent variables can be seen from the value of the Determination Coefficient (R²) of 0.857, or 85.7%, and the remaining 14.3% is explained by other factors outside the scope of this study. Thus, the hypothesis that there is a significant influence of the independent variables on the Employee Performance variable can be accepted.